The Mediterranean Diet, recognized by UNESCO as a cultural heritage of humanity (Italian Journal of Public Health, 2010)
The term “Mediterranean Diet” was coined, paradoxically, by Americans in the early’60s and today – only 50 years from the “discovery” of this characteristic, traditional food model – the UNESCO declares that this century-long cookery culture, belonging to populations overlooking the Mediterranean Basin, represents a “Cultural Heritage of Humanity”.
Keywords: Mediterranean Diet; UNESCO; eating habits; cardiovascular diseases prevention